Advanced Principles Governing the Comprehensive Management of Patients with Purulent Soft Tissue Wounds of the Upper and Lower Extremities - Nurboboyev Adhambek Uyg‘un o‘g‘li (INTEGRATION OF EDUCATION AND SCIENCE: GLOBAL CHALLENGES AND SOLUTIONS, 2026)
Hyperventilation combined with oxygen therapy creates new opportunities for optimizing wound healing processes and enhancing antimicrobial defense. This approach reduces the risk of acute complications, shortens the duration of hospitalization, and contributes to lowering overall healthcare costs. Recent studies confirm that oxygen therapy exerts a positive effect on cellular metabolism, angiogenesis, and anti-infective mechanisms. At the same time, determining the efficacy of hyperventilation in the management of upper and lower limb wounds, adapting it to the individual characteristics of patients, and preventing potential complications remain pressing scientific and clinical challenges. Therefore, the investigation of oxygen-flow–induced hyperventilation in the treatment of infected limb wounds is highly relevant not only from a theoretical perspective but also in practical terms, offering broad prospects for achieving improved outcomes in surgical practice. Objective of the Study: The aim of this study is to improve the treatment outcomes of patients with purulent surgical diseases of the soft tissues of the upper and lower limbs through the application of wound hyperventilation using an oxygen flow.